ANALISIS SISTEM DAN PROSEDUR AKUNTANSI ASET DI DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU DAERAH PROVINSI SULAWESI UTARA - Mentu, Dewi Kristanti; Pusung, Rudy J.; Suwetja, I Gede (Universitas Sam Ratulangi, 2018)
Local government assets are one of the elements of the regional government balance sheet, in the asset information the balance sheet report describes the condition of economic wealth owned by local governments. Analysis of local government assets is carried out to find out more about the wealth and economic potential of the local government so that from this information the public can assess various things. Accounting for assets is an economic resource that is controlled and owned by the local government. The asset accounting systems and procedures a controlling tool in managing assets used by the Regional Work Unit. The purpose of study was to find out how the systems and procedures for asset accounting in the Regional One-Stop Regional Service and Services Office of North Sulawesi Province. The method use in this research is descriptive analysis method. The result show that the application of system and procedure for asset accounting procedures is in accordance with the Regulation of the Minister of Home Affairs No. 17 of 2007. It is recommended that the asset accounting system and procedures at the One Door Investment Service from North Sulawesi. and Integrated Services in accordance with regulations and maintain them again by carrying out technical guidance and socialization to improve the quality of human resources.Keywords: systems, procedures, asset, accounting, analysis